Enhancing Military Training Using Extended Reality: A Study of Military Tactics Comprehension - Boyce, Michael W.; Thomson, Robert H.; Cartwright, Joel K.; Feltner, David T.; Stainrod, Cortnee R.; Flynn, Jeremy; Ackermann, Christian; Emezie, John; Amburn, Charles R; Rovira, Ericka (Frontiers in Virtual Reality, 2022)
This study identifies that increasing the fidelity of terrain representation does notnecessarily increase overall understanding of the terrain in a simulated mission planningenvironment using the Battlefield Visualization and Interaction software (BVI; formerlyknown as ARES (M. W. Boyce et al., 2017). Prior research by M. Boyce et al. (2019)compared human performance on a flat surface (tablet) versus topographically-shapedsurface (BVI on a sand table integrated with top-down projection). Their resultsdemonstrated that the topographically-shaped surface increased the perceived usability ofthe interface and reduced cognitive load relative to the flat interface, but did not effectoverall task performance (i.e., accuracy and response time). The present study extends thiswork by adding BVI onto a Microsoft HoloLens™. A sample of 72 United States MilitaryAcademy cadets used BVI on three different technologies: a tablet, a sand table (aprojection-based display onto a military sand table), and on the HoloLens™in awithin-subjects design. Participants answered questions regarding military tactics in thecontext of conducting an attack in complex terrain. While prior research (Dixon et al.,2009) suggested that the full 3D visualization used by the Hololens™should improveperformance relative to the sand table and tablet, our results demonstrated that theHoloLens™performed relatively worse than the other modalities in accuracy, response time,cognitive load, and usability. Implications and limitations of this work will be discussed.